Phenolic content and antioxidant capacity of Cypriot wines - Galanakis, Charis M.; Kotanidis, Anestis; Dianellou, Maria; Gekas, Vassilis (My University, 2015)
We characterised 12 wines (10 red, 1 sweet red, and 1 white) from different Cypriot cultivars in terms of their phenolic, anthocyanin composition, and antioxidant capacity as determined by two activities: radical scavenging and ferric reducing ability. Two different phenolic fractions (tannin-free and 1-kDa permeate) were also isolated from Cypriot wines with an ultimate goal of investigating their role in the overall antioxidant capacity of wines. The results indicated that Maratheftiko and Lefkada cultivars had higher concentrations of o-diphenols, hydroxycinnamic acid derivatives, flavonols and anthocyanins compared to other Cypriot cultivars like Ofthalmo, Mavro, and Giannoudi. The higher concentrations of phenols did not always correspond to a higher antioxidant capacity, probably due to the antagonistic action observed between hydroxycinnamic acid derivatives, flavonols, and anthocyanins. The latest interactions restricted the release of flavonols' advanced antiradical activity in wines.
Keywords: Anthocyanins; Antiradical activity; Flavonols; Hydroxycinnamic acid; o-diphenols